Demand for Emergency Services Trends in New South Wales Years 2010–2014 (DESTINY): Age and Clinical Factors Associated with Ambulance Transportation to Emergency Departments. (1st November 2016) - Dinh, Michael M.; Muecke, Sandy; Berendsen Russell, Saartje; Chalkley, Dane; Bein, Kendall J.; Muscatello, David; Nagaraj, Guruprasad; Paoloni, Richard; Ivers, Rebecca
Abstract : Objectives: The study aimed to analyze ambulance transportations to Emergency Departments (EDs) in New South Wales (NSW) and to identify temporal changes in demographics, acuity, and clinical diagnoses.Methods: This was a retrospective analysis of a population based registry of ED presentations in New South Wales. The NSW Emergency Department data collection (EDCC) collects patient level data on presentations to designated EDs across NSW. Patients that presented to EDs by ambulance between January 2010 and December 2014 were included. Patients dead on arrival, transferred from another hospital, or planned ED presentations were excluded.Results: A total of 10.8 million ED attendances were identified of which 2.6 million (23%) were transported to ED by ambulance. The crude rate of ambulance transportations to EDs across all ages increased by 3.0% per annum over the five years with the highest rate observed in those 85 years and over (620.5 presentations per 1, 000 population). There was an increase in the proportion of category 1 and 2 (life-threatening or potentially life-threatening) cases from 18.1% to 24.0%.Conclusion: Demand for ambulance services appears to be driven by older patients presenting with higher acuity problems. Alternative models of acute care for elderly patients need to be planned and implemented to address these changes.